Amino acid metabolism in tennis and its possible influence on the neuroendocrine system - Struder, H. K.; Hollmann, W.; Duperly, J.; Weber, K. (British Journal of Sports Medicine, 1995)
To investigate amino acid metabolism during endurance exercise as well as its influence on plasma prolactin (PRL) we subjected eight nationally ranked tennis players (mean(s.d.) age 25.6(2.8) years, mean(s.d.) weight 83.9(5.7) kg, mean(s.d.) height 184.4(4.6) cm) to 4h of continuous tournament tennis. Venous and capillary blood samples were taken before and after the exercise. Amino acids were measured by HPLC-fluorescence detection as o-phthalaldehyde derivatives; nonesterified fatty acids (NEFA), ammonia, total protein, glucose insulin and PRL by enzymatic methods. Exercise caused a decline of branched-chain amino acids (BCAA) by 28(14)%. Elevation of NEFA resulted in a significant mean(s.d.) increase of free tryptophan (TRP) (9.7(2.6) [pmol/microliter] vs 17.8(6.4) [pmol/microliter]. The mean(s.d.) ratio of free TRP:BCAA increased by 165%(90) which favours entry of free TRP into the brain. However, PRL did not change significantly. We conclude that during long-lasting interval sports BCAA contribute as energy substrates. Alterations in competition of amino acids at the blood-brain barrier favour entry of free TRP into the brain. PRL changes cannot be explained by the increase in plasma level of free TRP or the ratio of free TRP:BCAA.